Book Review - Marketing Research: A Practical Approach - Kumar, Manoj (Serbian Journal of Management, 2013)
Book: Marketing Research: A Practical Approach Author: Bonita Kolb Publisher: Sage Publications ISBN: 978-1-4129-4796-1 First Published: 2008 Reviewer: Manoj Kumar, Asst Professor, Indus Business Academy, Greater Noida, India